The population of insects in rubber nursery at RISDA Nursery and Landscape SDN BHD / Mohd Amirul Adam Abu Bakar - Abu Bakar, Mohd Amirul Adam (Faculty of Plantation and Agrotechnology, 2019)
Rubber known Hevea brasiliensis is a robust perennial crop native of South America. It a sources of natural rubber in produced the product from the latex. RISDA Nursery SDN BHD is the major supplier of rubber seedling for the smallholder around Kelantan. The objectives from this study is to determine the insects population in difference age of rubber seedling and to determine the significant interaction between of age of seedling and sampling time towards the population of insect. The insects was collected by using Yellow Sticky Trap, the trap was put in every plot of rubber seedling. Then, the data was collected in twice a week for duration 4 weeks in total. The data was analysed by using One-Way ANOVA with alpha (0.05). The results show 4 order was done be collected in all stage of age of rubber seedling which are 45 days, 2 month and 3 and half month. Then, the highest species have been collected in this study is Whitefly from Hemiptera. The orders were significant difference is Orthoptera and Coleoptera. These orders are significant on every stage of seedling ages. The age 2 months and 3 and half months is become a focus on insects as their host. In order to reduce pest infestation, the nursery manager should had to understand the pest status and also from this study the manager are able know the occurrence of the insects in their nursery especially Even though in controlling the insect pest, mostly farmer or growers are choose chemical.